Long-term acoustic monitoring at North Sea well site 22/4b. (December 2015) - Wiggins, Sean M.; Leifer, Ira; Linke, Peter; Hildebrand, John A.
Abstract: Marine seeps produce underwater sounds as a result of bubble formation and fragmentation upon emission from the seabed. The frequency content and sound levels of these emissions are related to bubble size distribution and emission flux, providing important information on methane release from the seafloor. Long-term passive acoustic monitoring was used to continuously record seep sounds over a 7-month period within the blowout crater at the abandoned well site, 22/4b, in the central North Sea. Also recorded were water column fluid velocities and near-seafloor water conductivity, temperature, and pressure. Acoustic signatures were primarily from ∼1 to 10 kHz. Key features were relatively broad spectral peaks at about 1.0, 1.5, 2.2, 3.1, 3.6 and 5.1 kHz. Temporal variations in spectral levels were apparently associated with tides. The recordings also documented a series of major episodic events including a large and persistent increase (∼10 dB) in overall sound levels and spectral broadening on 8 December 2011. The acoustic temporal pattern of this event was consistent with other recorded large transient events in the literature, and the major event was correlated with dramatic changes in other measurements, including increased water column fluid velocities, increased pressure and decreased salinity, indicating real changes in emission flux. Observed seabed morphology changes reported elsewhere in this special issue, also likely were related to this event. These data demonstrate the dynamic nature of marine seepage systems, show the value of monitoring systems, and provide direct supporting evidence for a violent formation mechanism of many widespread seep-associated seabed features like pockmarks. Highlights: First study using long-term passive acoustic monitoring of methane seeps at well blowout site 22/4b. Seep acoustic temporal variations correlated with ocean tides. Major acoustic transient event recorded on 8 December 2011 with high temporal resolution.